Understanding, Objectives and Scope of Islamic Educational Philosophy - Abdul Aziz Romdhoni (Al-Alim: Jurnal Pendidikan Agama Islam, 2025)
Islamic educational philosophy is a scientific discipline that discusses concepts, principles and values in Islamic education. This philosophy aims to provide a solid foundation for the development of Islamic education so that it is in accordance with the teachings of the Koran and Hadith. The study of Islamic educational philosophy covers various aspects, including the meaning, objectives, functions, scope and methods used in this study. Islamic education not only focuses on cognitive aspects, but also on the formation of character and morals that are in accordance with Islamic teachings. As time goes by, Islamic education faces various challenges, such as globalization, modernization and technological developments. Therefore, the study of Islamic educational philosophy is becoming increasingly important to ensure that the Islamic education system remains relevant and able to respond to the challenges of the times without losing the essence of Islamic values.